Computer-assisted sperm analysis of freshly diluted and stored Garole ram liquid semen - JOSHI, ANIL; BAG, SADHAN; MITTAL, J P (The Indian Journal of Animal Sciences, 2012)
Computer-assisted sperm analysis technique was used in this study to objectively evaluate sperm kinematics of 32 Garole ram semen ejaculates extended @ 1: 1 with egg yolk McIllvaine glucose diluent initially, and subsequently after 24 hr of storage at refrigeration temperature. Significant (P